2005
DOI: 10.1086/427238
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation of Cerebral Malaria and Severe Malarial Anemia

Abstract: Our data suggest strong familial aggregation of CM and SMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The odds of having cerebral malaria were 2.49 times higher for a child whose sibling had a history of cerebral malaria than the odds for a child whose sibling had no history of cerebral malaria (34,141). Similar results have been obtained for mild malaria and severe anemia (72,141). In addition, Mackinnon et al (97,98) found that genetic factors explained ϳ25% of the variation in the incidence of mild malaria episodes.…”
Section: Heritability Of Phenotypes Related To Malarial Infection Andsupporting
confidence: 56%
See 2 more Smart Citations
“…The odds of having cerebral malaria were 2.49 times higher for a child whose sibling had a history of cerebral malaria than the odds for a child whose sibling had no history of cerebral malaria (34,141). Similar results have been obtained for mild malaria and severe anemia (72,141). In addition, Mackinnon et al (97,98) found that genetic factors explained ϳ25% of the variation in the incidence of mild malaria episodes.…”
Section: Heritability Of Phenotypes Related To Malarial Infection Andsupporting
confidence: 56%
“…The results of several family studies have shown conclusively a familial aggregation of blood infection levels (1,52,142), malaria attacks (72), severe malaria (141), and antimalarial immune responses (12,155,158). Segregation analyses of parasitemia yielded significant sibling correlation coefficients, which ranged from 0.16 to 0.24 (1,52,142).…”
Section: Heritability Of Phenotypes Related To Malarial Infection Andmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included 341 children with SM (either CM or SA) and 42 children with uncomplicated malaria (UM) ( Table 1) hospitalized in the pediatric department of Gabriel Toure Hospital in Bamako, Mali [17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, because related individuals often share a common environment (such as a house), and environmental factors play a major role in the risk of infectious diseases, environmental and genetic effects are inseparable in most field study designs (for example, those that have pairs of full-sibs, each pair living in a different house [1,35]). In order to separate these effects, it is necessary to study sets of individuals of varying genetic relatedness who live together in the same house: information on genetically related individuals who live in different households also helps.…”
Section: Introductionmentioning
confidence: 99%